HEPATITIS C VIRUS INFECTION AND LYMPHOMA - Felipe Suarez; Caroline Besson; Emmanuel Bachy; Olivier Hermine (Mediterranean Journal of Hematology and Infectious Diseases)
Apart from its well known role as an etiological agent for non-A and non-B viral hepatitis, there is growing evidence that hepatitis C virus is associated to B-cell non-Hodgkin lymphoma. The association between HCV and lymphoproliferative disorders has been recently postulated based on epidemiological data, biological studies and clinical observations. Although various subtypes of lymphomas appear to be associated to HCV, diffuse large B-cell lymphoma, small lymphocytic lymphoma/chronic lymphocytic leukemia and marginal zone lymphoma appeared to be particularly represented among HCV-positive patients. The causative role of HCV in those disorders has been further supported by the response to anti-viral therapy. Despite a better understanding of pathophysiological processes at stake leading from HCV infection to overt lymphoma, many issues still need to be further elucidated. Although HCV has been demonstrated to directly infect peripheral blood mononuclear cells both in vitro and, in some cases, in vivo, a strong body of evidence rather supports the hypothesis of an indirect transformation mechanism by which sustained antigenic stimulation leads from oligoclonal to monoclonal expansion and sometimes to lymphoma, probably through secondary oncogenic events. Here, we review epidemiological and biological studies, as well as clinical data on antiviral therapy, linking HCV-infection to B-cell non-Hodgkin lymphoma.